Selenium WebDriver 3 practical guide : end-to-end automation testing for web and mobile browsers with Selenium WebDriver - Gundecha, Unmesh; Avasarala, Satya (Packt Publishing, 2018)
Real-world examples of cross-browser, mobile, and data-driven testing with all the latest features of Selenium WebDriver 3 Key Features Unlock the full potential of Selenium to test your web applications Use Selenium Grid for faster, parallel running, and cross-browser testing Test iOS and Android Apps with Appium Book Description Selenium WebDriver is an open source automation tool implemented through a browser-specific driver, which sends commands to a browser and retrieves results. The latest version of Selenium 3 brings with it a lot of new features that change the way you use and setup Selenium WebDriver. This book covers all those features along with the source code, including a demo website that allows you to work with an HMTL5 application and other examples throughout the book. Selenium WebDriver 3 Practical Guide will walk you through the various APIs of Selenium WebDriver, which are used in automation tests, followed by a discussion of the various WebDriver implementations available. You will learn to strategize and handle rich web UI using advanced WebDriver API along with real-time challenges faced in WebDriver and solutions to handle them. You will discover different types and domains of testing such as cross-browser testing, load testing, and mobile testing with Selenium. Finally, you will also be introduced to data-driven testing using TestNG to create your own automation framework. By the end of this book, you will be able to select any web application and automate it the way you want. What you will learn Understand what Selenium 3 is and how is has been improved than its predecessor Use different mobile and desktop browser platforms with Selenium 3 Perform advanced actions, such as drag-and-drop and action builders on web page Learn to use Java 8 API and Selenium 3 together Explore remote WebDriver and discover how to use it Perform cross browser and distributed testing with Selenium Grid Use Actions API for performing various keyboard and mouse actions Who this book is for Selenium WebDriver 3 Practical Guide is for software quality assurance/testing professionals, software project managers, or software developers interested in using Selenium for testing their applications. Prior programming experience in Java is necessary.